2019
DOI: 10.1136/flgastro-2018-101156
|View full text |Cite
|
Sign up to set email alerts
|

Comparing alternative follow-up strategies for patients with stable coeliac disease

Abstract: BackgroundOnce clinically stable, patients with coeliac disease should have annual follow-up. Lack of capacity in gastroenterology outpatient clinics mean alternatives are required.ObjectivesWe studied the effectiveness of follow-up deferred to general practitioners (GP-FU) and compared this with a neighbouring Trust where follow-up was through a dedicated nurse-led telephone clinic (T-FU).DesignAll patients with coeliac disease were posted a questionnaire examining patient satisfaction, adherence with gluten-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Croker et al 29 explored patient preferences for CD annual reviews; however, the delivery structure was not part of their study. Pritchard et al 30 reported CD follow-up provision by face-to-face appointment with a general practitioner (GP) compared with a nurse-led telephone clinic. Of the adults who were offered a telephone clinic, they were more likely to receive an annual review, have their symptoms assessed and their diet reviewed compared with those who had GP follow-up provision.…”
Section: Discussionmentioning
confidence: 99%
“…Croker et al 29 explored patient preferences for CD annual reviews; however, the delivery structure was not part of their study. Pritchard et al 30 reported CD follow-up provision by face-to-face appointment with a general practitioner (GP) compared with a nurse-led telephone clinic. Of the adults who were offered a telephone clinic, they were more likely to receive an annual review, have their symptoms assessed and their diet reviewed compared with those who had GP follow-up provision.…”
Section: Discussionmentioning
confidence: 99%
“…After correction of these disturbances, initiation of supplements for nutritional deficiencies and rigorous counseling, these patients are usually sufficiently stable to be discharged home. Strict adherence to a gluten-free diet and regular follow up with a care provider may prevent future hospitalizations and the development of complications [ 16 ]. In our study, from 2007-2017, a majority (68.17%) of the CeD hospitalizations were deemed stable enough to be discharged home; however, we noted a trend towards decreasing home discharges and an increasing trend for transfers to other facilities, such as skilled nursing facilities and intermediate care facilities, and discharge home with home healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Pritchard et al suggests that over 75% of CD patients have no primary care follow-up appointment, 33 despite the fact that telephone follow-up clinics have been shown to have a positive impact of GFD adherence in adults with CD. 34 This combined with the finding that 36.0% of gastroenterologists felt that doctors were not required for the management of CD and that 30% of all CD patients have non-responsive CD (defined as persisting symptoms despite being on a GFD), 35 suggests the need for an achievable, standardised national follow-up service for CD.…”
Section: Discussionmentioning
confidence: 99%